Konsekwencje członkostwa w Unii Europejskiej dla rynkowego finansowania mieszkalnictwa w Polsce - wybrane zagadnienia - Lis, Piotr (The Consequences of EU Membership for Market Financing of Housing in Poland, 2005)
The aim of this article entitled "The consequences of EU membership for market financing of housing in Poland" is to present the indications and prospects for market system of financing of housing in Poland as a result of EU membership. The coherence of housing sector with its surrounding and the housing policy which have been shown in the first part of paper, allowed to single out the elements of housing financing. The discussion in the subsequent parts of this article, which have been based on the theoretical framework are supported by examples of housing policy background in different countries undergoing economic transformations, EU-15 countries and euro zone.The membership of Poland in the European Union will favourably affect the position of the housing sector in the market aspect of long - term housing financing. There are to be few determining factors such as: more stable and lower inflation than during the process of economic transformation, lower interest rates in the phase of financial markets and policies integration within the monetary union and higher incomes when assuming the occurance of real convergence. The important role of housing policy which is slightly regulated by the EU should be stressed. Development barriers' liquidation and creation of convenient conditions for housing financing should be the main purpose of the housing policy. If these conditions are accomplished, EU membership of Poland may affect the further development of primary market financing housing, faster growth of the secondary market and the rising of derivative instruments market in the next phase.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 337-351